FAKTOR YANG BERHUBUNGAN DENGAN PEMANFAATAN ANTENATAL CARE (ANC) DI WILAYAH KERJA PUSKESMAS KECAMATAN LAWE SUMUR KABUPATEN ACEH TENGGARA TAHUN 2013 - Alas Sriwahyu; Yusniwarti Yusad; Erna Mutiara (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
ABSTRACT Antenatal Care (ANC) is a health service by skilled health personel to a women during her pregnancy, based on standard antenatal care stated in midwifery standard services (Standar Pelayanan Kebidanan = SPK). Based on data from the Ministry of Health Republic of Indonesia in 2012, the coverage of 1st visit of pregnant women in Indonesia was 95.71% and 4th visit was 88.27%. Report of health center of Lawe Sumur subdistrict in 2012, it was found that the coverage of 1st visit was 90.2% and 4th visit was 82%. This research aimed to know the factors related to the utilization of the ANC in the working area of health center of Lawe Sumur Subdistrict, Aceh Tenggara District in 2013. The research design was Cross Sectional study. The population is all of post partum mothers from January to March 2013 living in the working area of health center of Lawe Sumur Subdistrict, as many as 84 mothers and all of them were selected as samples. Data were collected by interview using questionnaires. Data analysis was done by univariate and bivariat analysis used Chi-Square test. The results showed that out of 84 mothers, only 26 mothers (31.0%) utilized the ANC. It’s found there was relationship between knowledge (p=0.001), parity (p=0.005), health personel’s support (p=0.001), trust (p=0.001), the family/husband’s support (p=0.001) and the utilization of ANC. It is expected to Lawe Sumur Subdistrict Health Center to increase extention about the benefit and the purpose of ANC examination, the importance of arranging pregnancy interval, the kind of ANC service which can be given by health center, to change postpartum mother’s perspective and make them believe, by increasing the experience of health center personel, taking training and involving traditional birth attendants and community leaders. Target of information providing is extended to the family or husband because their support have real influence on the utilization of ANC. Keywords : Antenatal Care, Knowledge, Health Personel Support, Trust, and Support Families/Husbands